ULASI IKAN BILIH (MYSTACOLEUSEUS PADANGENSIS) DI NAGARI SUMPUR KECAMATAN BATIPUH SELATAN KABUPATEN TANAH DATAR PROVINSI SUMATERA BARAT - Kusai '; Lamun Bathara; Leona Saputra (Berkala Perikanan Terubuk, 2014)
ABSTRACTThis study conducted on 30 August-22 September 2013 in the Sumpur village, South Batipuh District, Tanah Datar Regency West Sumatra Province. Aims of this study wasto determine the change in villagers'culture and local wisdom implementation of Sumpur to the preservation of Bilih fish populations in Batur lake. This studiy used a qualitative approach fenomologis method. Primary and secondary data collection used purposive sampling technique. Local Wisdom of Sumpur village under taken to the preservation of Bilih fish populations in Singkarak lake, because the people able to preserve the aquaticenvironmen of Lake Batur preserve fish populations bilih. There are interdependence between cultural change, implementation oflocal knowledge, as well asenvironmental sustainability.Keywords: Local Wisdom, Bilih, fenomologis